(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The main approach to the development of youth sports is the scientific study of the current provisions of the methodology of sports training. The implementation of the relevant provisions of youth sports has carried out a number of periods: from the study of individual industries characteristic of activities within the broad general publications of recent decades, in which significant patterns are deployed. Significant successes have been achieved at this stage. In general, it is acceptable to attribute that at the present time the following are among the most researched approaches to the system of development potential of a children’s and youth sports school: methods of developing mental abilities in the age aspect; a system for creating long-term training for young athletes; rationing and a system of preparatory loads; a system of selection of young chess players; a method of comprehensive verification in the preparation of students of sports schools; organizational and methodological base of youth sports. Based on the collected knowledge, the problem of personification of sports training is being intensively studied in the current period. During the preparation, a personal approach to the students should be observed, attention should be paid to their individual characteristics for the fullest development of physical qualities. One of the main approaches here was to study the methodology of the aspect under study. In addition, the personal specifics of the physical training of young athletes were developed during the periods of initial sports orientation and intensive training in the chosen sport.